Control of Chagas disease vectors - Ramsey JM; Schofield CJ (Instituto Nacional de Salud Pública, 2003)
Most Latin American countries are making dramatic progress in controlling Chagas disease, through a series of national and international initiatives focusing on elimination of domestic populations of Triatominae, improved screening of blood donors, and clinical support and treatment of persons infected with Trypanosoma cruzi. Some countries, particularly Uruguay, Chile and Brazil, are sufficiently advanced in their programmes to initiate detailed planning of the subsequent phases of Chagas disease control, while others such as Peru, Ecuador, and Mexico, are currently applying only the initial phases of the control campaigns. In this review, we seek to provide a brief history of the campaigns as a basis for discussion of future interventions. Our aim is to relate operational needs to the underlying biological aspects that have made Chagas disease so serious in Latin America but have also revealed the epidemiological vulnerability of this disease.